2006
DOI: 10.3727/000000006783981756
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Preservation at 10°C Minimizes Catalytic Iron, Oxidative Stress, and Cold-Induced Injury

Abstract: There is growing evidence that oxidative stress plays an important role in mediating the injury induced by hypothermia during the preservation of cells and tissues for clinical or research use. In cardiovascular allografts, endothelial cell loss or injury may lead to impaired control of vascular permeability and tone, thrombosis, and inflammation. We hypothesized that hypothermia-induced damage to the endothelium is linked to increases in intracellular catalytic iron pools and oxidative stress. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 54 publications
3
12
0
Order By: Relevance
“…Low cell viability (∼20%) seen at 4°C is in agreement with other studies that have shown cell viability ranging from ∼20% to ∼33% after storage at this temperature [5], [12]. Rewarming after cold-storage has been shown to induce mitochondrial swelling and initiate apoptosis, which may account for the high cell death seen at 4°C [23], [29]. Evidence of injury to epidermal cells associated with cold and re-warming seen at 4°C is particularly clinically relevant as refrigeration is the most common method of split skin graft storage and low cell viability may influence skin graft healing [5].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Low cell viability (∼20%) seen at 4°C is in agreement with other studies that have shown cell viability ranging from ∼20% to ∼33% after storage at this temperature [5], [12]. Rewarming after cold-storage has been shown to induce mitochondrial swelling and initiate apoptosis, which may account for the high cell death seen at 4°C [23], [29]. Evidence of injury to epidermal cells associated with cold and re-warming seen at 4°C is particularly clinically relevant as refrigeration is the most common method of split skin graft storage and low cell viability may influence skin graft healing [5].…”
Section: Discussionsupporting
confidence: 90%
“…The favorable conditions at 10°C were explained by minimal generation of catalytically available intracellular iron and reduced oxidative stress. Similarly, high proliferative capability was retained [23]. Higher cell viability, at approximately 60% or above, was shown in the present study at several temperatures (12°C, 24°C, 28°C, 32°C and 37°C), which is comparable to that reported in cultured epithelial autograft cryopreservation studies [27], [32].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The preservation of endothelial cells at 10°C can reduce oxidative stress and cold-induced injury [23]. In our work mammalian cells were able to maintain a considerably high level of viability and excellent recovery when stored at 16°C or 22°C for 4 days (Figs 1D and 2B–2D).…”
Section: Discussionsupporting
confidence: 54%